2020
DOI: 10.3892/etm.2020.9001
|View full text |Cite
|
Sign up to set email alerts
|

Biportal endoscopic decompression vs. microscopic decompression for lumbar canal stenosis: A systematic review and meta‑analysis

Abstract: Lumbar decompressive surgery is the gold standard treatment for lumbar spinal stenosis. Minimally invasive surgical techniques have been introduced with the aim of reducing the morbidity associated with open surgery. The purpose of the present study was to systematically search the literature and perform a meta-analysis of studies comparing the outcomes between biportal endoscopic technique and microscopic technique for lumbar canal stenosis decompression. A comprehensive search of the PubMed, Google Scholar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
2
21
2
Order By: Relevance
“…Two similar articles of systematic review and meta-analysis concluded that bi-portal endoscopic technique could be considered as an alternative to the microscopic decompression 20,21) . There were no significant differences in VAS score for leg and back pain, ODI at final follow-up between bi-portal endoscopic decompression and microscopic decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Two similar articles of systematic review and meta-analysis concluded that bi-portal endoscopic technique could be considered as an alternative to the microscopic decompression 20,21) . There were no significant differences in VAS score for leg and back pain, ODI at final follow-up between bi-portal endoscopic decompression and microscopic decompression.…”
Section: Discussionmentioning
confidence: 99%
“…When more levels are fused, the bleeding of the vertebral cancellous bone surface signi cantly increases. Anatomically, the management of hemorrhage in the lumbar spine with rich blood supply, especially the spinal venous plexus, is tricky [11,35,36]. And UBE surgery relies on continuous, large amounts of saline irrigation with certain pressure, resulting in more di culty in adequate hemostasis intraoperatively [11,37].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, open microsurgical decompression including microscopic decompression has been the gold standard treatment for lumbar spinal stenosis 3,9,15,16) . In recent years, endoscopic spinal surgery for lumbar spinal stenosis has been introduced and progressed 1,10,11,13,14) . In our results, there was no statistically significant difference in VAS-L, VAS-B, or ODI scores at one month or three months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar spinal stenosis is a clinically symptomatic condition caused by narrowing of the spinal canal that compresses nerve roots 1,14) . Most elderly people experience at least one episode of lower back pain, sciatica, claudication, or walking difficulty during their lives 3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation